Tratamento químico de sementes de soja: análise de imagem e metodologias para avaliação da qualidade fisiológica e impactos no cultivo - Rocha, Debora Kelli (2019)
The soy is one of the main cultivated species in the world, with great expression and high economic impact on Brazilian agribusiness. Currently, the demand of the seed market consists in the commercialization of treated seeds, and in the need to maintain the high physiological quality of the seeds, as well as representative in the assessment of the same. Therefore, there is a need for adaptation of methodologies of physiological analysis and improvement of techniques of analysis of images. The objective was to evaluate the influence of the treatment of soybean seeds with plant protection products by means of physiological analyzes, including new methodologies, analysis of image and the impacts on the culture in the field. The experiments were installed in collaboration between the laboratory Qualiteste and the Federal University of Uberlândia (UFU). The study was divided into two experiments. The first involved 9 treatments of seeds with different phytosanitary products (Fungicides and insecticides) and adjustments and new methodologies of evaluation of germination, being they: between paper - BP, between sand - BS, between paper with water restriction - BPR, between paper with pre-conditioning - BPC, sand between paper - SBP and vermiculite between paper - VBP. The treatments with insecticide molecules affected the germination and seedling evaluation, with greater phytotoxicity in relation to fungicides. Methodologies with readily available water resulted in greater phytotoxicity. For the evaluation of soybean germination treated with phytosanitary products the BPC, SBP and VBP methodologies were the most appropriate. In the second experiment, the seeds were treated with the same products and in 2 seasons, anticipated (60 days) and at the time of sowing in the field. The seeds were analyzed by means of physiological tests and measurements performed with Vigor-S® software. The image analysis was efficient for the initial detection of seed / seedling phytotoxicity in function of the seed treatment, especially root length. The insecticides Pirâmide®, Cruiser® and Cropstar® depreciated the seed vigor mainly with the anticipation of treatment. The anticipation in 60-days of seed treatment, although affecting the initial development of plants for the products tested, did not affect the productivity in the field due to vigor.